2021
DOI: 10.1038/s41598-021-87121-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive surgical treatment strategy for spinal metastases

Abstract: The management of patients with spinal metastases (SM) requires a multidisciplinary team of specialists involved in oncological care. Surgical management has evolved significantly over the recent years, which warrants reevaluation of its role in the oncological treatment concept. Any patient with a SM was screened for study inclusion. We report baseline characteristics, surgical procedures, complication rates, functional status and outcome of a large consecutive cohort undergoing surgical treatment according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 70 publications
(14 reference statements)
1
29
1
3
Order By: Relevance
“…Current treatment concepts of spinal metastases include stereotactic radiosurgery, conventional radiotherapy, and surgery 7 . According to Wagner et al, surgical management should generally represent the first step of a conclusive treatment algorithm, although it should be promoted by an interdisciplinary team 8 . Our patient underwent 28 cycles of radiotherapy after the first surgery and was free of symptoms until the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment concepts of spinal metastases include stereotactic radiosurgery, conventional radiotherapy, and surgery 7 . According to Wagner et al, surgical management should generally represent the first step of a conclusive treatment algorithm, although it should be promoted by an interdisciplinary team 8 . Our patient underwent 28 cycles of radiotherapy after the first surgery and was free of symptoms until the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, structural stabilization requires screw fixation [ 20 , 21 ] that consists of inserting different kinds of implants such as pedicle screws in the vertebra [ 20 , 22 ]. Following screw fixation, surgery complications can arise, e.g., construct failure, malposition of screws, neurologic deterioration, and deep and superficial wound infections [ 21 , 23 , 24 ]. Several retrospective studies have investigated complication rates after screw fixation for the treatment of spinal metastases, reporting between 15 and 47% of revisions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown that spinal surgery, mainly spinal instrumentation with decompression, for metastatic epidural spinal cord compression (MESCC) significantly improves pain, neurologic function and health-related quality of life [ 2 , 3 ]. Consecutively, surgery for SM has gained a decisive role in modern interdisciplinary oncological treatment [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…While SMs are the most frequent neoplasms of the spine, being found in about 15–35% of cancer patients [ 8 , 9 ] primary bone tumors of the spine are rare (less than 5% of spinal neoplasms) [ 10 ]. Treatment decisions are made interdisciplinary and individually, taking into account the patient’s symptoms, the degree of osteolytic instability, the degree of epidural compression, the radio- and chemosensitivity of the tumor and the overall prognosis [ 4 , 11 ].…”
Section: Introductionmentioning
confidence: 99%